The impact of gratitude on adolescent materialism and generosity. Issue 4 (4th July 2019) - Chaplin, Lan Nguyen; John, Deborah Roedder; Rindfleisch, Aric; Froh, Jeffrey J.
ABSTRACT: Despite decades of research on materialism, there are few viable strategies for reducing materialism in younger consumers. In this paper, we present two studies conducted among over 900 adolescents that reveal a promising strategy for decreasing materialism: fostering gratitude. In Study 1, results from a nationally representative survey showed that children and adolescents with a grateful disposition were less materialistic. In Study 2, experimental evidence showed that an intervention designed to increase gratitude (i.e. keeping a gratitude journal) significantly reduced materialism among adolescents and also attenuated materialism's negative effect on generosity. Using real money and donation as a behavioral measure, we found that adolescents who kept a gratitude journal donated 60% more of their earnings to charity compared to those in the control condition. We discuss the implications of our findings, offer some suggestions for putting our results into action, and provide an agenda for future research in this domain.